ORGANIZATIONAL AND MANAGEMENT APPROACH TO THE DESIGN OF THE EDUCATIONAL ENVIRONMENT OF THE CHILD’S PERSONALITY - Гонтаровська, Н. Б. (Pedagogy of Higher and Secondary Education, 2011)
The scientific research presents an innovative experience of pedagogical group of the highest Ukrainian level experimental educational establishment, the educational complex No 28 of Dnipropetrovs’k on creation of the educational environment of child’s development. In particular, the article considers the organization and manage approach in project of its components: a social, technological, space and objects subjects of educational process. The author describes the systematic model of educational environment in the meaning of management of quality management; states the main principles, functions and methods of pedagogical management’s system.